PENGARUH KOMPENSASI KERJA TERHADAP KINERJA PEGAWAI INSEMINATOR DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PETERNAKAN DAN PERIKANAN KABUPATEN SITUBONDO - Meirilia, Niken; Karnadi, Karnadi; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Human resources are one of the most important factors in a company or organization and affect the development of a company so that it can grow rapidly if it has competent human resources in its field. Success in achieving company goals effectively and efficiently is one of the factors that are carried out by human resources. The purpose of this study was to analyze and examine the effect of work compensation on employee performance inseminators with work motivation as an intervening variable. The population in this study is the Inseminator of the Department of Animal Husbandry and Fisheries of Situbondo Regency. The sampling technique was determined by saturated sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). Hypothesis test results direct effect using the Smart PLS 3.0 application, compensation has a significant positive effect on motivation, compensation has a significant positive effect on performance, motivation has a significant positive effect on performance. The results of the indirect effect hypothesis test show that the compensation variable on performance through motivation has a significant positive effect.